2006
DOI: 10.1063/1.2349483
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear compressibility effects in fluid-structure interaction and their implications on the air-blast loading of structures

Abstract: The impulse imparted by a blast wave to a freestanding solid plate is studied analytically and numerically focusing on the case in which nonlinear compressibility effects in the fluid are important, as is the case for explosions in air. The analysis furnishes, in effect, an extension of Taylor’s pioneering contribution to the understanding of the influence of fluid-structure interaction (FSI) on the blast loading of structures [The Scientific Papers of Sir Geoffrey Ingram Taylor, edited by G. K. Batchelor (Cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
116
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 16 publications
4
116
0
Order By: Relevance
“…0.25 kg PE4 hemispherical explosive charges were detonated 4 m, 6 m, 8 m and 10 m away from and orthogonal to the external wall of a reinforced concrete bunker, forming a large, effectively rigid target, such that fluid-structure interaction effects [26,27] could be ignored. The charges were detonated on a 50 mm thick steel plate, placed on a level, flat concrete ground slab, enabling the detonation to be considered as a hemispherical surface burst.…”
Section: E Ex Xp Pe Er Ri Im Me En Nt Ta Al L V Va Al Li Id Da Amentioning
confidence: 99%
“…0.25 kg PE4 hemispherical explosive charges were detonated 4 m, 6 m, 8 m and 10 m away from and orthogonal to the external wall of a reinforced concrete bunker, forming a large, effectively rigid target, such that fluid-structure interaction effects [26,27] could be ignored. The charges were detonated on a 50 mm thick steel plate, placed on a level, flat concrete ground slab, enabling the detonation to be considered as a hemispherical surface burst.…”
Section: E Ex Xp Pe Er Ri Im Me En Nt Ta Al L V Va Al Li Id Da Amentioning
confidence: 99%
“…Recent analytical [9] and numerical [18,19] assessments indicate the FSI effect is much weaker in air and only becomes significant when (i) the overpressure is high, (ii) the core crush strength is small and (iii) the face sheet exposed to the impulse has a very low mass (inertia) per unit area. Even so, recent experiments and confirmatory numerical simulations have shown that sandwich panels with thick, strong square honeycomb cores and thick face sheets still showed significantly reduced back face deflections compared to equivalent solid plates subjected to the same very high intensity (20-35 kPa.s) impulsive loads in air [1].…”
Section: Introductionmentioning
confidence: 99%
“…In United States, FEMA 426 [4] provides the design measurements to reduce physical damage to the structural and non-structural components of building and related infrastructures during conventional bomb attacks, as well as attacks using chemical, biological and CBR agents. Kambouchev et al [5] discussed the nonlinear compressibility effects in fluid-structure interaction and their implications on the air-blast loading of structures. Blanc et al [6] discussed empirical method to estimate the blast loading.…”
Section: Introductionmentioning
confidence: 99%